2010
DOI: 10.1001/archdermatol.2010.245
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Study of Hidradenitis Suppurativa Following Long-Pulsed 1064-nm Nd:YAG Laser Treatment

Abstract: To assess clinical and histopathologic changes occurring after long-pulsed 1064-nm Nd:YAG laser treatment of hidradenitis suppurativa (HS). Design: Prospective, controlled clinical and histologic study of patients with Hurley stage II HS disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 27 publications
2
43
0
7
Order By: Relevance
“…The long-pulsed neodymium:yttrium-aluminium-garnet (Nd:YAG) laser is a device that has traditionally been used for hair removal, but has recently shown promise in clearing old lesions of HS and preventing new eruptions. In accordance with studies in the current literature, we hypothesize that the Nd:YAG laser will significantly improve subjects with hidradenitis suppurativa compared to standard, uninvasive treatment with topical antibiotics [1,2]. Study aims include: to treat subjects with hidradenitis suppurativa with Nd:YAG laser therapy once monthly for 3 consecutive months, with a one month followup; to compare the effectiveness of Nd:YAG treatment on one side of the subject (e.g., right) to treatment with topical antibiotics on the subject's other side (e.g., left); to assess treatment response using a visual analogue scale; to assess subject satisfaction with treatment using a questionnaire; and to photodocument treatment response at each visit.…”
supporting
confidence: 84%
“…The long-pulsed neodymium:yttrium-aluminium-garnet (Nd:YAG) laser is a device that has traditionally been used for hair removal, but has recently shown promise in clearing old lesions of HS and preventing new eruptions. In accordance with studies in the current literature, we hypothesize that the Nd:YAG laser will significantly improve subjects with hidradenitis suppurativa compared to standard, uninvasive treatment with topical antibiotics [1,2]. Study aims include: to treat subjects with hidradenitis suppurativa with Nd:YAG laser therapy once monthly for 3 consecutive months, with a one month followup; to compare the effectiveness of Nd:YAG treatment on one side of the subject (e.g., right) to treatment with topical antibiotics on the subject's other side (e.g., left); to assess treatment response using a visual analogue scale; to assess subject satisfaction with treatment using a questionnaire; and to photodocument treatment response at each visit.…”
supporting
confidence: 84%
“…Xu et al conducted a study assessing the clinical and histopathologic changes at different time points over 2 monthly sessions, with a 2-month follow-up thereafter, on 19 patients using the long-pulsed Nd:YAG laser. There was a 31.6% improvement in the laser-treated areas over all anatomic sites using the modified HS-LASI scoring system [31]. There was increased inflammation 1 week after treatment, followed by decreased inflammation, fibrosis and scarring at 1 and 2 months post-treatment with the laser.…”
Section: Infrared Lasers 1064 Nm Nd:yag Lasermentioning
confidence: 89%
“…Some patients reported increased tenderness and drainage 1 week after treatment, followed by rapid disease improvement, similar to the incision and drainage procedure. The Nd:YAG laser showed destruction of organized inflammatory lesions in the superficial to mid-dermis [31]. In all of the three studies using Nd:YAG for HS, single pass was performed on the affected region, and pulse stacking was performed two to three times on inflamed nodules, abscesses and fistulae [29][30][31].…”
Section: Infrared Lasers 1064 Nm Nd:yag Lasermentioning
confidence: 99%
See 1 more Smart Citation
“…1 Reported improvement rates range from 31.6% to 72.7%. 128,129 Intense pulse light (IPL) used in a prospective trial of 18 patients, showed a 55% reduction of the Sartorius score compared to 10% on the untreated side. 130 Photodynamic therapy (PDT), reported in more than 20 HS patients, 1 has been described to have good to mediocre efficacy.…”
Section: -Lasers and Lightsmentioning
confidence: 99%